EFFECT OF FECB GENE POLYMORPHISM ON DIFFERENT REPRODUCTIVE TRAITS IN BLACK BENGAL GOAT - Kumar, Vivek; Kumar, Nandani; Singh, Lal Babu; Kumar, Subodh (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
The aim of this study was to investigate FecB gene polymorphism in Black Bengal goats and its effect on different reproductive traits like age at first kidding, service period, kidding interval and gestation period. A total 96 DNA samples (42 males and 54 females) were subjected to polymerase chain reaction to obtain amplified fragments of 190 bp. These fragments were allowed for polyacrylamide gel electrophoresis for the detection of Single Strand Conformational Polymorphism (SSCP). Polymorphism was revealed and three different SSCP variants were found which were designated as AA, AB and BB. The highest genotype frequency was observed for AB (0.38), which was followed by BB (0.33) and AA (0.29). Least-square analysis of variance showed non-significant effect of genotype on age at first kidding, service period, kidding interval and gestation Period. It suggested that genetic factor responsible for these traits is not related to this mutation.
Keywords: FecB; Black Bengal Goat; PCR-SSCP; Reproductive traits